2015
DOI: 10.21168/rbrh.v20n2.p523-532
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-six years of uneven changes in low flows due to different uses and operation of a large dam in a semiarid river

Abstract: Little is known about the hydrological impact of the dams in Brazil, despite the rising energy demand and untapped potential. The Paraguaçu River's discharge has been greatly impacted since 1986 by a large dam built in the lower course of the river. In the 26 years of the history of the dam, the minimum discharges have followed different operational guidelines: 1) there was no established discharge minimum between 1987 and 1996; 2) the discharge minimum was 11 m³s-1 between 1997 and 2004; and 3) hydropower gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Moreira et al (2014) experimentally showed high mortality rates of T. tagusensis and T. coccinea when exposed to low salinity (i.e., 0, 5, 10 practical salinity units). However, the Tubastraea invasion in the Paraguaçu estuary may have occurred due to the predominance of marine salinity levels (Genz et al, 2008;Reis-Filho et al, 2010;Genz & Lessa, 2015). This condition is likely to be associated with the building of the Pedra do Cavalo Dam in 1985 and Pedra do Cavalo Hydroeletric Power Plant in 2005 on the upper estuary (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreira et al (2014) experimentally showed high mortality rates of T. tagusensis and T. coccinea when exposed to low salinity (i.e., 0, 5, 10 practical salinity units). However, the Tubastraea invasion in the Paraguaçu estuary may have occurred due to the predominance of marine salinity levels (Genz et al, 2008;Reis-Filho et al, 2010;Genz & Lessa, 2015). This condition is likely to be associated with the building of the Pedra do Cavalo Dam in 1985 and Pedra do Cavalo Hydroeletric Power Plant in 2005 on the upper estuary (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2D), the dry season on the coast. With the construction of Pedra do Cavalo dam (4.63 × 10 9 m 3 volume) in 1986, built for urban water supply, flood control, and hydroelectric power generation, the Paraguaçu River discharge became highly regulated (Genz and Lessa 2015). While the average river discharge for the period 1986 to 2015 was 69.0 m 3 /s, the average flow released by the dam was 55.3 m 3 /s.…”
Section: Study Areamentioning
confidence: 99%
“…The BTS is the third largest Brazilian estuary where the drainage of a catchment area over 60 × 10 3 km 2 (twice the size of Hudson River or 1.2 times larger than Weser watersheds) is vital to maintain an estuarine circulation during the dry season on the coast (Santana et al 2018). Its most important river, draining more than 90% of the catchment area, was dammed in the 1980s for flood control, urban water supply, and hydroelectricity generation, and since then, a significant part of the riverine flow, already impacted by increasingly smaller precipitation in its catchment, does not reach the bay (Genz and Lessa 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in this study showed notable differences between sites in (Genz et al, 2006), it may also hinder the impacts of a possible reduction of the transport of suspended particulate material to the Bay. It is noteworthy that Paraguaçu is a relatively small river (annual mean discharge of 72 m 3 s -1 , Genz and Lessa, 2015) that, despite its large drainage area, drains Proterozoic, mostly crystalline rocks (Souza et al, 2004) in a large semi-arid region, and transports a relatively small amount of solids (Hatje and Barros, 2012).…”
Section: Sedimentation Ratesmentioning
confidence: 99%